COOLING BEHAVIOUR OF PARTIAL THERMOREMANENCES INDUCED IN MULTIDOMAIN MAGNETITE - Muxworthy A.R. (My University, 2000)
The cooling behaviour of partial thermoremanences (pTRMs) below the acquisition temperature (T2) is reported for the first time for well defined, sized, synthetic multidomain magnetite samples produced by hydrothermal recrystallisation. The pTRM cooling behaviour of low-stress magnetite samples is similar but not identical to that reported for higher stress crushed magnetite samples, that is, it displays a decrease in pTRM on cooling below T2, indicating domain re-organisation. This agrees with recent kinetic theories and domain observations, but strongly disagrees with the classical hysteretic models based on Néel’s ideas which assume that the remanence increases with the increase in spontaneous magnetisation. It is demonstrated that the rate of decrease in remanence on cooling is not a viscous effect, and the rate of decrease increases with inducing field dependency. pTRM acquired from the Curie temperature Tc (pTRMTcT2) is found to be more stable to cooling than pTRM acquired from a temperature T1 which is less than Tc (pTRMT1T2). It is suggested that for low-stress samples, pTRM acquired at high temperatures has a wider range of metastable stable states available than pTRM acquired at lower temperatures. The results support the theories that domain wall nucleation is relatively easy during cooling. Differences between the cooling behaviour of the low-stress samples and those previously published for crushed magnetite samples can be attributed to differences in the dislocation densities and the available metastable domain states.